Interrupted Magnetic First Order Transitions and Kinetic Arrest probed with In-field Neutron Diffraction. (September 2016) - Siruguri, V.; Kaushik, S.D.; Rayaprol, S.; Babu, P.D.; Chaddah, P.; Sampathkumaran, E.V.; Hoser, A.; Ritter, C.
Abstract: In-field neutron diffraction studies were carried out on two compounds that exhibit magnetic first order phase transitions (FOPT). It is shown that the FOPT can be interrupted by an external magnetic field, resulting in a coexistence of kinetically arrested metastable states and equilibrium phases. Use of a novel protocol CHUF (Cooling and Heating under Unequal Fields) helps to determine the coexisting phase fractions and also to observe the devitrification of the kinetically arrested phase into the equilibrium phase, in a manner similar to that found in structural glassy systems.